First experience with a ready-to-use solution for remote monitoring of patients suffering from heart failure. (11th May 2021) - Lemieux, H; Picard, F; Barritault, F; Labarre, J; Lafitte, S; Maribas, P; Chaouky, H; Abdennadher, M; Lasserre, R; Amara, W; Pages, N; Nisse-Durgeat, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Heart failure (HF) is associated with a high mortality rate and recurrent hospitalizations. Purpose: To present the first data of the patients using Satelia® Cardio solution Method: Satelia® Cardio is a HF patient management solution with a remote monitoring system and a therapeutic guidance by a dedicated-nurse phone platform, supported by the ETAPES Program. The system is accessible from any device and requiring no installation. After the inclusion, the patient is contacted by the nurse, he then receives an SMS alerts following cardiologist prescription (on regular basis), with a link leading to a web page on which he will answer 7 questions and enter his current body weight. Satelia® Cardio algorithm is based on these data inputs, their variability, and the weight. In case of worsening of symptoms, the cardiologist will be notified. Since Covid-19 lockdown, more than 1400 patients have been monitored with the solution. Results: 165 centers (306 cardiologists) are using Satelia® Cardio with 3540 HF patients monitored in the last 29 months. The patients with a mean age of 72 years (19-100) are predominantly males (67%), and mostly NYHA II/III (69%/31%) with a mean LVEF of 40%. The adherence to the system is very good (91%) with 78% of patients still monitored (n = 2787). The main reasons for stopping are related to the occurrence of death (205/753) or patient/HCP decision (392/753), or other reasons (156/753). Over the period of analysis, the HF patients answered to 163 700 questionnaires, generating 8210 alerts transmitted to the referent cardiologists. Conclusion: Patient management solution with a remote monitoring system is key to improving the follow-up of HF patients. The solution Satelia® Cardio is an easy way to use a web application to monitor HF patients, especially on the current period of Covid-19 with a low rate of premature discontinuation. A further step will be to initiate studies to assess the potential benefits for both patients and HCPs of such remote monitoring solution in HF.